Developing Conversational Interfaces for iOS Add Responsive Voice Control to Your Apps - Mitrevski, Martin (Apress, 2018)
Learn how to incorporate your own conversational interfaces into iOS applications. This book will help you work comfortably with multiple frameworks, including Apple's Speech and SiriKit frameworks; Google's API.AI conversational interfaces platform; and Facebook's Wit.ai. You'll explore the basics of natural language processing on iOS and see how to develop sentiment analysis with Apple's new Core ML framework. You'll also understand the primary challenges of conversational interfaces, and how to future proof your design. With the introduction of SiriKit and the Speech framework, iOS developers now have huge opportunities to incorporate conversational interfaces into their apps. The latest advancements in natural language processing and machine learning allow for the development of complex conversational interfaces. This book incorporates all aspects of conversational interfaces on iOS-from voice transcription to natural language processing and entities extraction to text to speech commands.